Dilated neonatal cisterna magna and Marfan syndrome. (29th July 2011) - Vasu, Vimal; Child, Anne H; Modi, Neena; Rutherford, Mary; Cowan, Frances
Abstract : The authors report the incidental finding of a dilated cisterna magna with an abnormal configuration to the falx in a newborn infant with Marfan syndrome who was recruited to a research study involving whole body MRI. To our knowledge, dilation of the cisterna magna has not previously been reported in patients with Marfan syndrome. Potential implications for antenatal diagnosis, the ethics of recruiting healthy volunteers for research and directions for future work are discussed.